2020
DOI: 10.13106/jafeb.2020.vol7.no11.747
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Bank Regulation and Supervision on the Efficiency of Islamic Banks

Abstract: This study investigates the impact of bank regulation and supervision on the efficiency of banking sectors on 108 Islamic banks from 26 countries offering Islamic banking and finance products and services. The technical efficiencies of individual Islamic banks have been analyzed using the data envelopment analysis method (DEA). The ordinary least square estimation method is employed to examine the impact of country supervision and regulation on the technical efficiency of Islamic banks. The empirical findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Similarly, results shown in columns (2)–(5) reveal that at the 1% alpha level, corruption control, government effectiveness, regulatory quality and rule of law, respectively, exert significant positive effect on financial institution efficiency among economies in SSA. These findings are consistent with expectations and theoretical supposition as alluded to by Beck et al (2001), Rajan and Zingales (2001) and Mohd Noor et al (2020). The results highlight the view that improved institutional and governance structures to some extent spurs effectiveness and efficiency in various facets of governmental and regulatory organizations, leading to delivery of strategies that improve key sectors of an economy including the operations of financial institutions.…”
Section: Empirical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, results shown in columns (2)–(5) reveal that at the 1% alpha level, corruption control, government effectiveness, regulatory quality and rule of law, respectively, exert significant positive effect on financial institution efficiency among economies in SSA. These findings are consistent with expectations and theoretical supposition as alluded to by Beck et al (2001), Rajan and Zingales (2001) and Mohd Noor et al (2020). The results highlight the view that improved institutional and governance structures to some extent spurs effectiveness and efficiency in various facets of governmental and regulatory organizations, leading to delivery of strategies that improve key sectors of an economy including the operations of financial institutions.…”
Section: Empirical Analysissupporting
confidence: 89%
“…The results showed that financial reform, ownership and listing of banks significantly affect bank efficiency; the study again found no conclusive evidence in relation to the nexus between size and efficiency. Mohd Noor et al (2020) found from a study that used data from 108 Islamic banks from 26 countries that supervisory power, activity restrictions and private monitoring exert significant positive effect on Islamic banks’ efficiency. The study again revealed that less stringent capital requirement improves the technical efficiency of Islamic banks for Middle East and North Africa and middle-income countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, inflation, stock exchange listings and revenue diversification were found to have significant negative impacts on cost efficiency. Mohd Noor et al . (2020) studied similar interactions using data from 108 Islamic banks in 26 countries.…”
Section: Related Literaturementioning
confidence: 99%
“…Recently, the researcher has also shown interest in empirically testing the association between regulation and other dimensions of the banking industry. For example, association between bank regulation and efficiency (Noor et al [24], Li, [25], Dudchenko et al [26], Chortareas et al [15], Djalilov and Piesse [3], Triki et al [16]), bank regulation and level of completion (Li,[25], Hakenes and Schnabel [27], Degryse and Ongena [28], Agoraki et al [29], Yin [30]), bank regulation and financial stability of banks (Anarfo et al [31], Schnabl and Sonnenberg [32], Fraccaroli et al [33]), and bank regulation and risk-taking behavior (Brandao-Marques et al [34], Bartholdy and Justesen [35] 2021, Louhichi et al [36], Hilscher et al [37]) were a few focus areas which are also being scrutinized in the bank regulation literature. Furthermore, Figure 1 represents the research trend in bank regulation and supervision literature (see Additional Points).…”
Section: Relevant Literature Reviewmentioning
confidence: 99%